Internal and External Carriage of Inoculated Salmonella in Broiler Chickens - Cason, J.A.; Buhr, R.J.; Richardson, L.J.; Cox, N.A. (International Journal of Poultry Science, 2007)
External and internal persistence of inoculated Salmonella and spread to uninoculated broiler chicks in the same pens were studied by sampling ceca and rinses of feathered carcasses in two experiments. Half of the day-old chicks in pens were orally inoculated with a nalidixic-acid-resistant strain of Salmonella Typhimurium at three levels of inoculum (0.1 mL delivering approximately 4 X 102, 104, or 106 cfu). At 3, 6, and 8 weeks of age, equal numbers of inoculated and non-inoculated pen mates were individually electrocuted and rinsed in 400 mL of diluent, after which ceca were removed aseptically, with a total of 654 chickens sampled in the two experiments. There were no differences in Salmonella incidence between inoculated and non-inoculated birds at any age, so the marker Salmonella was well distributed within pens. Total incidence was 70%, 86%, and 83% at the 102, 104, and 106 inoculum levels, respectively. Considering both cecal and rinse samples, incidence was 81%, 84%, and 72% at 3, 6, and 8 weeks of age respectively. There were 95 positives in the cecal samples only, 149 positives in the rinses only, and 277 positives in both ceca and rinse samples, so sampling either ceca or carcass rinses alone underestimated the total incidence of the marker Salmonella.